(untitled) (Archives of Mechanics - Test, 2023)
This paper firstly expands an efficient numerical methodology developed from the source panel method to the added mass calculation of long column systems in fluid. Structures submerged in fluid are considered as two-dimensional and are discretized into a number of source panels. The influence coefficient matrices and the potential function are then calculated and the fluid forces are calculated by the unsteady Bernoulli equation. Finally, we utilize this present method to calculate the mass coefficients of some typical problems, which effectively verifies its feasibility and accuracy. This method takes into account both applicability and computational efficiency. On the one hand, in contrast to the analytical method which is only applicable to specific cross-sections, this method is applicable to arbitrary boundaries with C0 continuity in mathematics. On the other hand, this method requires less mesh and computation than commercial software. This paper extends the application of the source panel method which is widely used in aerodynamics to provide a reference for added mass calculation problems in engineering.